The Influence of Antenatal Health Education on Pregnant Women’s Knowledge of Pregnancy Danger Signs in The Galala Community Health Center Work Area - Juwita Juwita; Anik Sri Purwanti (Jurnal Rumpun Ilmu Kesehatan, 2026)
Background: Pregnancy is a critical period requiring comprehensive knowledge of danger signs to prevent maternal and fetal complications. Health education during antenatal care is crucial in increasing pregnant women’s knowledge and awareness these danger signs. Previous studies in Indonesia have shown that structured antenatal education improves maternal knowledge, encourages timely health-seeking behavior, and reduces the risk maternal morbidity and mortality (Sari, 2020; Putri, 2021). Despite ongoing efforts, gaps in knowledge persist in many communities, including in the Galala work area, highlighting the need for targeted educational interventions. Objective: This study aims to examine the influence of antenatal health education on pregnant women’s knowledge of pregnancy danger signs in the Galala The intervention consisted of structured antenatal health education sessions covering common pregnancy danger signs, preventive measures, and the importance timely medical consultation. The Wilcoxon signed-rank test was used to analyze differences knowledge levels before and after the intervention, with a significance level set at p < 0.05. Results: All 30 participants received the health education intervention. Post-intervention assessments showed a significant improvement in knowledge levels, with the Wilcoxon test yielding p-value of 0.000. This indicates that antenatal health education had statistically significant effect on enhancing pregnant women’s knowledge of danger signs during pregnancy. Conclusion: Antenatal health education effectively improves pregnant women’s knowledge of pregnancy danger signs. Structured and targeted educational interventions by health professionals, particularly during routine antenatal visits, can empower women to recognize early warning signs and take timely action, thereby contributing to better maternal and fetal health outcomes.